Essential issues on solving optimal power flow problems using soft-computing - Chan, Kit Yan; Yu, Changjun; Teo, Kok Lay; Nordholm, Sven (American Institute of Mathematical Science, 2014)
Optimal power ow (OPF) problems are important optimization problems in power systems which aim to minimize the operation cost of generators so that the load demand can be met and the loadings are within the feasible operating regions of the generators. This brief paper emphasizes two essential issues related to solving the OPF problems and which are rarely addressed in recent research into power systems: 1) the necessity to validate operational constraints on OPF, which determine the feasibility of power systems designed for the OPF problems; and 2) and the necessity to developconventional methods for solving OPF problems which can be more effective than the commonly-used heuristic methods.